LINGUISTIC AND GENDER FOUNDATIONS OF ADVERTISING TEXTS - Shaimova Dildora Baxodirovna; Jurayeva Iroda Axmedovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the linguistic structure of advertising texts and the ways gender is constructed and represented within advertising discourse. Drawing on theories of discourse analysis, gender linguistics, and pragmatics, the study examines how language choices in advertising reflect and reinforce gender stereotypes while simultaneously adapting to contemporary social transformations. The research focuses on lexical, stylistic, and pragmatic features of advertising texts aimed at male and female audiences. The findings demonstrate that advertising discourse employs gender-specific linguistic strategies to influence consumer perception and behavior. At the same time, emerging trends toward gender-neutral and inclusive advertising reveal a gradual shift in communicative practices.